Adsorption of phosphorus onto nanoscale zero-valent iron/activated carbon: removal mechanisms, thermodynamics, and interferences. Issue 1 (12th January 2022) - Adly, Adel; Mostafa, Nagwan G.; Elawwad, Abdelsalam
Abstract: This study investigated removal mechanisms, thermodynamics, and interferences of phosphorus adsorption onto nanoscale zero-valent iron (nZVI)/activated carbon composite. Activated carbon was successfully used as support for nZVI particles to overcome shortcomings of using nZVI include its tendency to aggregate and separation difficulties. A comprehensive characterization was done for the composite particles, which revealed a high specific surface area of 72.66 m 2 /g and an average particle size of 37 nm. Several adsorption isotherms and kinetic models have been applied to understand the removal mechanisms. Adsorption isotherm is best fitted by Freundlich and Langmuir models, which indicates that the estimated maximum phosphorus adsorption capacity is 53.76 mg/g at pH 4. Adsorption kinetics showed that the chemisorption process behaved according to a pseudo-second-order model. An adsorption mechanism study conducted using the intra-particle diffusion and Boyd kinetic models indicated that the adsorption rate is limited by surface diffusion. A thermodynamic study showed that phosphorus removal efficiency increased as the solution temperature increased from 15 to 37 °C. Finally, the results of an interference study showed that the presence of Ni 2+, Cu 2+, Ca 2+, Na + cations, nitrate ions ( ), and sodium acetate improves removal efficiency, while the presence of sulfate ions ( ) and urea reduces removal efficiency. HIGHLIGHTS: Successful synthesis of nZVI/AC composite with a specific surface area of 72.66 m 2 /g. Characterization of the composite using SEM, EDX, XRD, BET SSA, FTIR, and TAG. Langmuir adsorption isotherm model is best fitted phosphorus adsorption on nZVI/AC. nZVI/AC composite had a superior phosphorus adsorption capacity was 53.76 mg/g. Phosphorus adsorption rate was controlled by surface diffusion. Graphical Abstract